Otimização de um modelo hidrossedimentalógico em regiões semiáridas - Arruda, Petley de Medeiros (2011)
The degradation of water quality and quantity are among the major environmental problems, which the society is facing today. Environmental managers use computer modeling to simulate and to better understand the natural phenomena that occur in watersheds, in order to assist the planning of the use and preservation of natural resources. Among several existing models, there is the WESP model (Watershed Erosion Simulation Program), which wasdeveloped in order to simulate the hydrological response of small basins. Considering these and other facts, the aim of this study is to evaluate the performance of two optimization algorithms to calibrate the WESP model, in order to simulate the runoff-erosion processes within the semiarid area of Paraiba state. This calibration was performed using the optimization methods RPS (Repulsive Particle Swarm) and DE (Differential Evolution),expecting to find the best set of parameters to be used in the modeling. Subsequently, it was performed a comparison between the observed and calculated runoff, and between the observed and calculated sediment yield. The results show that the automatic calibration routine RPS obtained a more satisfactory set of parameters, and converged with a reduced number of interactions, when compared to the DE optimization method.